2019
DOI: 10.33889/ijmems.2019.4.2-037
|View full text |Cite
|
Sign up to set email alerts
|

Kaizen a Tool for Continuous Quality Improvement in Indian Manufacturing Organization

Abstract: Kaizen is a practice of continuous improvements in manufacturing, assembly, quality and engineering. In this paper author have discussed the problems faced by a leading automobile manufacturing organization on quality of interior parts of the automobile like plastics and rubber. During study author used a new technique called “Global Customer Audit” which is basically a vehicle audit from final customer point of view for interior parts of automobiles. During this audit, author has observed various defects and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 18 publications
3
12
0
6
Order By: Relevance
“…It includes a number of isolated tools, including organizational culture, openness to employee suggestions, work in small groups, for example, in quality circles. There are approaches when other tools of lean production are included in the kaizen, for example, general maintenance of equipment, a "just-in-time" production system (Kumar, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…It includes a number of isolated tools, including organizational culture, openness to employee suggestions, work in small groups, for example, in quality circles. There are approaches when other tools of lean production are included in the kaizen, for example, general maintenance of equipment, a "just-in-time" production system (Kumar, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Different scholars also identified Kaizen practices as independent variables: leadership or top management support (Shafiq et al , 2019; Jong et al , 2019; Rawashdeh, 2018; Baye and Raju, 2016; Jalu, 2015; Beshah and Kitaw, 2014); Customer focus (Jong et al , 2019; Rawashdeh, 2018; Baye and Raju, 2016; Beshah and Kitaw, 2014); People management (Shafiq et al , 2019; Jong et al , 2019; Rawashdeh, 2018; Baye and Raju, 2016); Process management (Shafiq et al , 2019; Jong et al , 2019; Rawashdeh, 2018; Baye and Raju, 2016; Beshah and Kitaw, 2014); Continuous improvement (Rawashdeh, 2018; Baye and Raju, 2016); Product design (Psomas et al , 2014); Supplier quality management (Rawashdeh, 2018; Baye and Raju, 2016); Strategy (policy, strategic planning) (Shafiq et al , 2019; Jong et al , 2019; Rawashdeh, 2018); Resources including partnership (Shafiq et al , 2019; Beshah and Kitaw, 2014); Measurement, analysis and knowledge management (Jong et al , 2019; Rawashdeh, 2018); Kaizen tools and techniques (Jalu, 2015). Moreover, other preceding studies also identified Kaizen practices as CSFs: leadership (Janjić et al , 2019; Hailu et al , 2017b); Top management policy, commitment, support (Kumar, 2019; Lina and Ullah, 2019; Todorovic et al , 2019; Abdulmouti, 2018; Hailu et al , 2017b); process control (2017b); Culture of effective and flexible suggestion system (Kumar, 2019; Abdulmouti, 2018; Hailu et al , 2017b); the use of problem-solving approach (Kumar, 2019; Abdulmouti, 2018; Khanna et al , 2017a, b; Amrutkar and Kamalja, 2017) and Supportive organization structure (Kumar, 2019; Janjić et al , 2019); employee's attitude (Hailu et al , 2017b); employee's and management involvement, team dynamics (good presentation and communication skills), recognition (Janjić et al , 2019; Abdulmouti, 2018; Hailu et al , 2017b); good management–employee relationship and train employees (T...…”
Section: Literature Reviewmentioning
confidence: 93%
“…Kaizen is a Japanese word, which implies any change for good. It implies that continuously done small changes help in improving manufacturing techniques and processes (Kumar, 2019). Kaizen focuses on simplification by breaking down complex processes into subprocesses and then fix it.…”
Section: Kaizen Work Culture For Continuous Improvement With Value Chain Analysis Methodsmentioning
confidence: 99%